2006
DOI: 10.1007/s10584-006-6336-6
|View full text |Cite
|
Sign up to set email alerts
|

Learning with Local Help: Expanding the Dialogue on Climate Change and Water Management in the Okanagan Region, British Columbia, Canada

Abstract: The research activity described in this report is a comprehensive regional assessment of the impacts of climate change on water resources and options for adaptation in the Okanagan Basin. The ultimate goal of the project is to develop integrated climate change and water resource scenarios to stimulate a multistakeholder discussion on the implications of climate change for water management in the region.The paper describes two main objectives: (a) providing a set of research products that will be of relevance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 21 publications
3
50
0
2
Order By: Relevance
“…[WGII 14.5.1] • To cope with a 15% increase in heavy precipitation, Burlington and Ottawa, Ontario, employed both structural and non-structural measures, including directing downspouts to lawns in order to encourage infiltration, and increasing depression and street detention storage (Waters et al, 2003). [WGII 14.5 Columbia produced a water management plan in 2004 for a planning area known as the Trepanier Landscape Unit, which explicitly addresses climate scenarios, projected changes in water supply and demand, and adaptation options (Cohen et al, 2004;Summit Environmental Consultants, 2004 …”
Section: Adaptationmentioning
confidence: 99%
“…[WGII 14.5.1] • To cope with a 15% increase in heavy precipitation, Burlington and Ottawa, Ontario, employed both structural and non-structural measures, including directing downspouts to lawns in order to encourage infiltration, and increasing depression and street detention storage (Waters et al, 2003). [WGII 14.5 Columbia produced a water management plan in 2004 for a planning area known as the Trepanier Landscape Unit, which explicitly addresses climate scenarios, projected changes in water supply and demand, and adaptation options (Cohen et al, 2004;Summit Environmental Consultants, 2004 …”
Section: Adaptationmentioning
confidence: 99%
“…Tisdell (2010) evaluated the implications of different water policy options in a semiarid area of Australia by modelling and found that the most cost effective option was a reduction of the water allocation to entitlement holders in order to increase water available for environmental use. Similarly to our study, Cohen et al (2006) identified, by combining computer-based models and participatory research in the Okanagan Basin (Canada), a portfolio of adaptation options for water resources management rather than seeking consensus on the Bbest^option or process. Méndez et al (2012) explored the historical records of the Doñana case study to develop a tailored action research program and provide specific policy-relevant recommendations for water resources management and wetland conservation.…”
Section: Discussionmentioning
confidence: 96%
“…Recent researches have combined both methods to assess and identify climate change risk and adaptation options with valuable results on the adoption of a local adaptation strategy (Picketts et al 2013;Cohen et al 2006). Tisdell (2010) evaluated the implications of different water policy options in a semiarid area of Australia by modelling and found that the most cost effective option was a reduction of the water allocation to entitlement holders in order to increase water available for environmental use.…”
Section: Discussionmentioning
confidence: 99%
“…In the Canadian portion of the CRB, Cohen et al (2006) examined water supply and demand in the semi-arid Okanagan basin, with consideration of future scenarios of moderate to severe climate change. Sullivan et al (2003), for example, developed a water poverty index (WPI) to identify areas facing severe Water Resource Vulnerability in the Columbia River Basin / 341 water stress in South Africa.…”
Section: Introduction a Water Sustainabilitymentioning
confidence: 99%